2021
DOI: 10.1002/jimd.12428
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of arimoclomol in Niemann‐Pick disease type C: Results from a double‐blind, randomised, placebo‐controlled, multinational phase 2/3 trial of a novel treatment

Abstract: Niemann-Pick disease type C (NPC) is a rare, genetic, progressive neurodegenerative disorder with high unmet medical need. We investigated the safety and efficacy of arimoclomol, which amplifies the heat shock response to target NPC protein misfolding and improve lysosomal function, in patients with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…Even with access to next‐generation sequencing, difficulties in establishing a diagnosis of NPC often arise, for example when trying to decipher identified variants of unknown significance. Hence, the development of robust disease‐specific markers for diagnosis, accurate disease monitoring, and assessment of efficacy of emerging novel, targeted therapies 5 is crucial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with access to next‐generation sequencing, difficulties in establishing a diagnosis of NPC often arise, for example when trying to decipher identified variants of unknown significance. Hence, the development of robust disease‐specific markers for diagnosis, accurate disease monitoring, and assessment of efficacy of emerging novel, targeted therapies 5 is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, early detection is paramount for patients with disorders affecting the developing brain or resulting in neurodegeneration in order to achieve the best clinical outcomes 3 . This is more pertinent in the current era of personalized medicine, where an ever‐increasing number of novel, targeted, and disease‐specific therapeutic approaches are becoming available for neurological diseases that in the past were considered untreatable 4–6 …”
mentioning
confidence: 99%
“…Accordingly, efforts have been made to identify drug candidates that lead to upregulation of NPC1 variant expression, thereby increasing the NPC1 functional capacity. This resulted, among others, in the identification of ryanodine receptor antagonists [31], histone deacetylase inhibitors (HDACi, [32,33]) and arimoclomol [34,35] to modulate the NPC1 folding environment.…”
Section: Discussionmentioning
confidence: 99%
“…Various strategies are currently being studied to overcome this caveat, and recently, the intraventricular administration of ERT has been shown to be effective in neuronal ceroid lipofuscinosis type 2 22. Depending on the neurometabolic disease, increasing the enzyme activity may be possible through other strategies than ERT: (1) the administration of a high-dose vitamin or an enzymatic cofactor , such as vitamin B6 (pyridoxine) in certain forms of classic homocystinuria (cystathionine beta-synthase deficiency)23; (2) the administration of a molecule with a chaperone effect that will limit enzyme degradation, like migalastat in Fabry disease or arimoclomol in Niemann-Pick C disease (that increases heat shock protein expression)24 25; (3) haematopoietic stem cell transplant of cells expressing a normal activity of the deficient enzyme, whether allogenous (classically used in X-ALD, Krabbe disease and metachromatic leucodystrophy)26–28 or ex vivo genetically modified autologous stem cells expressing the deficient enzyme in a supraphysiological manner (recent trials have demonstrated the efficacy of this latter strategy in children with X-ALD and metachromatic leucodystrophy)29 30; and (4) liver and/or kidney transplant with restricted indications in organic acidurias and UCDs. Without directly acting on enzyme activity, some treatments similarly aim to support the deficient metabolic function: this mainly concerns defects of energy metabolism (Glut1 deficiency, PDC deficiency and mitochondrial beta-oxidation disorders) for which specific ketogenic diets can restore energy production, bypassing the altered energetic pathway.…”
Section: Key Concepts In Neurometabolic Diseasesmentioning
confidence: 99%